Representações murais de embarcações antigas na Fábrica da Pólvora de Barcarena: sua tipologia, cronologia e significado: DOI: https://doi.org/10.5281/zenodo.7920560 - Cardoso, João Luís; Martins, Adolfo Silveira; Teixeira, António; Oliveira, Rui; Sousa, Vítor Rafael Cordeiro de (Estudos Arqueológicos de Oeiras, 2023)
This study makes known the representations of vessels identified in three sectors of the walls of the road that accompanies and delimits the former Fábrica da Pólvora de Barcarena and in a wall located inside it. The location of these representations, almost entirely corresponding to fine line incisions, are associated with the production of gunpowder in the so‑called “Fábrica de Cima”, rebuilt and expanded by Lieutenant‑General Bartolomeu da Costa, which came into operation shortly after 1786, having continued in laboration in the 19th century. It was admitted that the typology of the sailing vessels represented, the majority of commerce, although some of war were identified, with the representation of their artillery, can be explained by the presence in the place of sailors of the respective crews that would participate in the transport of the gunpowder to the coast of the Tagus river, located about 6 km away. Indeed, at least in the case of the most relevant representation, its characteristics denounce someone who knew the particularities of naval architecture at that time, to which, evidently, the powder workers would be completely alien. On the other hand, the systematic association of these representations with apotropaic symbols, such as pentagrams, crosses and croziers, in addition to signatures or phrases still under study and interpretation, can be explained by the danger related to the handling, loading and transport of gunpowder, which was then ensured by large and heavy carts harnessed to oxen. The results obtained make known a reality until now completely unknown, which is urgent to preserve, and whose investigation is importante to continue.